「フジ」 コウロ (1976-1977) ニ オケル ヒョウメン カイスイ チュウ ノ クロロフィル α リョウ - 福地, 光男; フクチ, ミツオ; Fukuchi, Mitsuo (国立極地研究所, 1977)
P(論文) 1976年11月から1977年4月まで,第18次南極地域観測隊の海洋生物定常観測の一環として,「ふじ」の航路に沿って表面海水の採水およびクロロフィル-α量の測定を150点において実施した.クロロフィル-α量の分布は,概して過去の観測結果と似ていた.プリンスオラフ海岸沖のパックアイス域において最高値(2.40 mg/m^3)が見られた.また,セレベス海,マカッサール海峡およびマラッカ海峡においても高い値が観測された. During the relief cruise of the FUJI to Syowa Station, Antarctica, from November 1976 to April 1977, the chlorophyll-α contents in the surface water were measured at 150 stations as a part of the routine observations of marine biological program of the 18th Japanese Antarctic Research Expedition. The chlorophyll-α distributions were generally similar to those noticed in the previous observations. The maximum value was observed in the pack ice area of Prince Olav Coast, Antarctica (2.40 mg chl-α/m^3). The high values were also seen in the Celebes Sea, Makassar and Malacca Straits. departmental bulletin paper